2019
DOI: 10.1210/js.2019-mon-165
|View full text |Cite
|
Sign up to set email alerts
|

MON-165 The Risk of Developing Cardiovascular Diseases Increases with Age in Type 2 Diabetes Mellitus Patients in Yenagoa, Bayelsa State, Niger Delta Region of Nigeria

Abstract: Background and objective: Patients with type 2 Diabetes mellitus (DM) are known to be at risk of developing cardiovascular diseases (CVD). The prevalence and incidence of DM patients with heart diseases is unknown in Yenagoa and its environ of Bayelsa State, Niger Delta Region of Nigeria. The study investigated the incidence of CVD in chronic DM patients and compared the prevalence in both male and female subjects with respect to the duration of illness. The goals of screening are to improve life ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Similar results were previously reported [25,26]. The significant elevation of LDH, CK and CKMB in T2DM with CVD may be explained by their specificity to CVDs diagnostic and our founding agree with others studies that illustrated cardiac enzymes have been demonstrated to be important prognostic determinants to identify high-risk patients [23,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were previously reported [25,26]. The significant elevation of LDH, CK and CKMB in T2DM with CVD may be explained by their specificity to CVDs diagnostic and our founding agree with others studies that illustrated cardiac enzymes have been demonstrated to be important prognostic determinants to identify high-risk patients [23,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 93%
“…In DM, increased oxidants and lipid peroxides correlated with the decrease of antioxidant levels [10]. Previous studies exhibited a reduction of antioxidant levels in diabetic patients [11], [12]. SOD synthesis is regulated by specific SOD gene sequences.…”
Section: Introductionmentioning
confidence: 99%